A negative electrode active material for a secondary battery and a secondary battery
By optimizing the particle size distribution and compaction density of the negative electrode active material, a negative electrode diaphragm that meets specific relationships is designed, which solves the problem of lithium dendrites growing during the fast charging of lithium batteries, and achieves a balance between fast charging and long life. Improves battery safety and performance.
Patent Information
- Application Number
- CN202210824641.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-14
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2042-07-14
AI Technical Summary
Existing lithium batteries are prone to growth of lithium dendrites during fast charging, resulting in increased polarization of the battery, reduced power performance and safety hazards, and it is difficult to take into account both fast charging and long life.
By optimizing the particle size distribution, compaction density and specific surface area relationship of the negative electrode active material, a negative electrode diaphragm that satisfies 0.75≤Z≤1.5 was designed, and combined with graphite, soft carbon and other materials, a fast charging capacity and long cycle life was prepared. Negative pole film.
The fast charging capability and long cycle life of lithium-ion batteries are achieved, and the growth of lithium dendrites is avoided, and the safety and performance stability of the battery are improved.
Smart Images

Figure SMS_1 
Figure HDA0003745956050000011 
Figure HDA0003745956050000012
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium batteries, and in particular relates to a negative electrode active material of a secondary battery and a secondary battery. Background Art
[0002] Rechargeable batteries have outstanding features such as light weight, high energy density, no pollution, no memory effect, and long service life, so they are widely used in mobile phones, computers, home appliances, power tools and other fields. Among them, charging time and service life are increasingly valued by end consumers and are also important factors limiting the popularization of rechargeable batteries.
[0003] In order to shorten the charging time, the battery must have the ability to charge quickly. If the battery itself does not have the ability to charge quickly, it will be easy for lithium dendrites to grow on the negative electrode surface, which will lead to a series of adverse effects on the battery, such as increased battery polarization, decreased battery power performance, and a sharp shortening of battery life. At the same time, during the use of the battery, the continuous growth of lithium dendrites may pierce the isolation membrane and cause an internal short circuit, which will bring safety hazards to the battery.
[0004] From a technical point of view, the key to determining the charging speed of a battery is the negative electrode. Therefore, providing a negative electrode that can be charged quickly is a problem to be solved. Summary of the invention
[0005] In view of this, the technical problem to be solved by the present invention is to provide a negative electrode active material for a secondary battery and a secondary battery, and the negative electrode active material provided by the present invention has fast charging capability.
[0006] The present invention provides a negative electrode sheet of a secondary battery, wherein the negative electrode sheet comprises a negative electrode membrane and a negative electrode current collector, wherein the negative electrode membrane comprises a negative electrode active material, and wherein the negative electrode membrane satisfies 0.75≤Z≤1.5, wherein Z=0.0452*PD 负 *S 负 *D 50负 ,
[0007] PD 负 is the compaction density of the negative electrode membrane;
[0008] D 50负 is the median particle size of the negative electrode active material, in μm;
[0009] S 负 is the specific surface area of the negative electrode active material.
[0010] Preferably, 0.75≤Z≤1.
[0011] Preferably, 1.2 g / cm 3 ≤PD 负≤1.8g / cm 3 .
[0012] Preferably, 5.0 μm ≤ D 50负 ≤20μm.
[0013] Preferably, 1.0m 2 / g≤S 负 ≤2.5m 2 / g.
[0014] Preferably, the negative electrode active material is selected from one or more of graphite, soft carbon, hard carbon, carbon fiber, and mesophase carbon microbeads.
[0015] Preferably, the graphite is selected from one or more of artificial graphite, natural graphite and modified graphite.
[0016] Preferably, at least a portion of the negative electrode active material is in the form of secondary particles.
[0017] The present invention also provides a method for preparing the negative electrode sheet of the above-mentioned secondary battery, comprising the following steps: after mixing the negative electrode active material, conductive agent, thickener and binder, adding solvent deionized water, stirring until the system is uniform, and obtaining negative electrode slurry; uniformly coating the negative electrode slurry on the negative electrode collector, drying, and then cold pressing and cutting to obtain the negative electrode sheet.
[0018] Preferably, the mass ratio of the negative electrode active material, the conductive agent, the thickener and the binder is 95.4:1.9:0.9:1.8.
[0019] The present invention also provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet is the above-mentioned negative electrode sheet.
[0020] Compared with the prior art, the present invention provides a negative electrode sheet of a secondary battery, wherein the negative electrode sheet comprises a negative electrode membrane and a negative electrode current collector, wherein the negative electrode membrane comprises a negative electrode active material, and wherein the negative electrode membrane satisfies 0.75≤Z≤1.5, wherein Z=0.0452*PD 负 *S 负 *D 50负 , P.D. 负 It is the ratio of the mass of the membrane powder per unit area of the negative electrode after cold pressing to the volume of the powder; D 50负 It is the particle size corresponding to the cumulative volume percentage of the negative electrode active material reaching 50%, in μm; S 负 The invention obtains a secondary battery with fast charging capability and long cycle life by matching the relationship between the particle size distribution, compaction density and surface area of the battery graphite negative electrode active material. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a SEM image of the negative electrode active material used in Example 8;
[0022] Figure 2 This is a SEM image of the negative electrode active material used in Example 9. DETAILED DESCRIPTION
[0023] The present invention provides a negative electrode sheet of a secondary battery, characterized in that the negative electrode sheet comprises a negative electrode membrane and a negative electrode current collector, the negative electrode membrane comprises a negative electrode active material, and the negative electrode membrane satisfies 0.75≤Z≤1.5, wherein Z=0.0452*PD 负 *S 负 *D 50负 ,
[0024] PD 负 is the compaction density of the negative electrode membrane;
[0025] D 50负 is the median particle size of the negative electrode active material, in μm;
[0026] S 负 is the specific surface area of the negative electrode active material.
[0027] In the present invention, the negative electrode membrane satisfies 0.75≤Z≤1.5, preferably 0.75≤Z≤1.0, and further Z can be selected from 0.75, 0.8, 0.85, 0.9, 0.95, 1.0, or any value between 0.75 and 1.0.
[0028] Where Z = 0.0452*PD 负 *S 负 *D 50负 ,
[0029] The above relationship involves several key physical parameters that affect fast charging performance. In order to pursue fast charging performance of the battery, the negative electrode needs to meet the following conditions: 1. The particle specific surface area S is as large as possible to increase the number of channels for lithium ions to embed in the negative electrode layer; 2. The negative electrode particles are as small as possible, that is, D50 representing the particle size is as small as possible to increase the diffusion distance of lithium ions inside the negative electrode particles; 3. The PD compaction density is moderate, and the gaps between particles are moderate to avoid reducing the contact area between the electrolyte and the negative electrode particles; but while pursuing fast charging, it is necessary to consider the increase in specific surface area, which leads to an increase in interfacial side reactions, which has an adverse effect on the cycle and life. Under the requirements of both fast charging and life, a balanced design of physical parameters is required. However, PD 负 , S 负 , D 50负 The value ranges of these parameters are also limited.
[0030] Among them, PD 负 is the compaction density of the negative electrode membrane; PD 负 The compaction density is the ratio of the mass of the diaphragm powder per unit area of the electrode after cold pressing to the volume of the powder. The method for measuring the compaction density is a method known to those skilled in the art, that is, using a ten-thousandth caliper to measure the thickness d1 of the diaphragm and the thickness d2 of the current collector after cold pressing, and using a one-ten-thousandth gram precision balance to measure the mass m1 of the diaphragm per unit area S' and the mass m2 of the current collector per unit area after cold pressing, then PD 负 The calculation formula is: PD 负 =(m1-m2) / (S'*(d1-d2)). In the present invention, the compaction density PD of the negative electrode active material is 负 1.2~1.8g / cm 3 , preferably 1.2, 1.4, 1.6, 1.8, or 1.2 to 1.8 g / cm 3 In the present invention, the compaction density of the negative electrode active material needs to be controlled within a range of 1.2 to 1.8 g / cm 3 If the compaction density is too large, the impedance of the battery will increase, and the fast charging performance will deteriorate. If the compaction density is too small, the capacity per unit volume will be low, the internal resistance will be large, and the fast charging performance will also deteriorate.
[0031] D 50负 The median particle size of the negative electrode active material, that is, the particle size corresponding to the cumulative volume percentage of the negative electrode active material reaching 50%, is expressed in μm. According to the national standard GB / T 19077-2016 Particle Size Distribution Laser Diffraction Method, the sample is dispersed under pressure and the particle size of the material is characterized by a laser particle size analyzer. The test results are expressed as the median particle size D 50负 In the present invention, the median particle size D of the negative electrode active material is 50负 is 5 to 20 μm, preferably 5, 10, 15, 20, or any value between 5 and 20 μm. In the present invention, the median particle size D of the negative electrode active material needs to be 50负Controlled within the range of 5 to 20 μm, if the particle size of the negative electrode active material is too large, the chemical reaction speed will be slow, and the particles will easily break, resulting in increased internal resistance and impedance, which will affect the fast charging performance. When the particles of the negative electrode active material are small, the van der Waals force that needs to be overcome when lithium ions are embedded can be smaller, and the embedding is easier to carry out. Moreover, the smaller the particles, the more channels there are for lithium ion embedding and extraction, which is more conducive to quickly reaching a fully embedded lithium state, and the higher the high current charge and discharge performance. However, the particles of the negative electrode active material cannot be too small. If the particles are too small, the larger the specific surface area that can be in contact with the electrolyte, the more active lithium is consumed by the SEI film formed during the first charge and discharge process, and the greater the irreversible capacity loss. In the subsequent charge and discharge process, after the SEI film is destroyed, the SEI film will also consume active lithium during the repair process, the reversible capacity will be reduced, and the cycle performance will deteriorate.
[0032] S 负 It is the specific surface area of the negative electrode active material. The test is carried out according to the national standard "GB / T 19587-2004 Method for Determining the Specific Surface Area of Solid Matter by Gas Adsorption BET Principle", and the test is carried out using an adsorption characterization analyzer. The powder sample to be tested is placed in a U-shaped sample tube, and a mixed gas containing a certain proportion of adsorbate flows through the sample. The adsorption amount of the adsorbate molecule (N2) of the sample to be tested is determined based on the change in gas concentration before and after adsorption, and the specific surface area S is calculated. 负 In the present invention, the specific surface area S of the negative electrode active material is 负 1.0~2.5m 2 / g, preferably 1.0, 1.5, 2.0, 2.5, or 1.0 to 2.5m 2 When the specific surface area of graphite particles is controlled within an appropriate range, lithium ion embedding can be more easily performed, which is conducive to quickly reaching a fully embedded lithium state, that is, the high current charge and discharge performance is better.
[0033] Several key factors affecting fast charging performance involved in this relationship also have mutual constraints. D50 will affect the specific surface area of the negative electrode. Generally, the smaller the D50, the larger the specific surface area, and the better the fast charging performance; the smaller the D50, the larger the specific surface area, and the lower the compaction that the electrode can achieve. If D50 is too large, it will indirectly affect the reduction of S negative. If D50 is too large and S negative is too small, it will increase the impedance of the battery cell and reduce the charging capacity. In order to balance the impact on the charging capacity, the electrode design will reduce PD and increase the contact between particles and electrolyte to improve the overcharge capacity.
[0034] The parameters in the relationship restrict each other. At the same time, the requirements for physical properties of fast charging performance and life cycle are different. In order to meet the fast charging and life requirements of the battery, the physical parameters are designed in a balanced manner. The value of the formula Z composed of each parameter is within this range. On the basis of meeting the fast charging requirements, the cycle performance can be guaranteed.
[0035] In the present invention, the negative electrode active material is selected from one or more of graphite, soft carbon, hard carbon, carbon fiber, mesophase carbon microspheres, silicon-based materials, tin-based materials, and lithium titanate. Among them, the graphite is preferably one or more of artificial graphite, natural graphite, and modified graphite.
[0036] In the present invention, at least a portion of the negative electrode active material is in the form of secondary particles. The particle structure of the negative electrode active material is often divided into primary particles and secondary particles. The primary particles have high compaction density, small specific surface area, good high temperature performance and long life; the secondary particles often have strong fast charging capabilities, because the secondary particles are granulated and sintered from small-diameter primary particles. Within the same compaction density and particle size range, the secondary particles have a larger specific surface area, and the diffusion distance of lithium ions inside the particles is shorter, which is more conducive to fast charging.
[0037] During the sintering process of the secondary particles, some materials with binder functions such as asphalt are needed to stick them together in advance, and then sinter them at high temperature and graphitize them. Among them, the commonly used characterization method for particle structure is SEM, which can have a very clear resolution for secondary particles.
[0038] The present invention also provides a screening process for the negative electrode sheet of a secondary battery. Specifically, the present invention first screens the negative electrode active material and then controls the membrane parameters. Specifically, first select the median particle size D 50 The specific surface area S of the negative electrode active material in the range of 5 to 20 μm 负 1.0~2.5m 2 / g range of negative electrode active materials, and then control the compaction density of the membrane to be between 1.2 and 1.8 g / cm 3 .
[0039] In the negative electrode sheet design of the present invention, the compaction density PD of the negative electrode film is 负 , median particle size D of negative electrode active material 50 , the specific surface area S of the negative electrode active material 负 Taking all factors into consideration, when the negative electrode membrane satisfies 0.75≤Z≤1.5, the fast charging and cycle performance of the battery can be taken into account, and a secondary battery with fast charging capability and long cycle life can be obtained.
[0040] The compaction density PD of the negative electrode membrane can be adjusted by controlling the cold pressing parameters of the electrode. The median particle size D50 of the negative electrode active material and the specific surface area S of the negative electrode active material can be adjusted by selecting appropriate negative electrode materials.
[0041] The present invention also provides a method for preparing the negative electrode sheet of the secondary battery, comprising the following steps:
[0042] 1. After mixing the negative electrode active material, conductive agent, thickener and binder, add deionized water as solvent and stir until the system is uniform to obtain negative electrode slurry;
[0043] 2. The negative electrode slurry is uniformly coated on the negative electrode current collector, dried, and then cold pressed to adjust the compaction density and cut to obtain negative electrode sheets, so that the negative electrode film in the obtained negative electrode sheets meets the above-mentioned condition of 0.75≤Z≤1.5.
[0044] The negative electrode active material is the negative electrode active material described in the negative electrode sheet, which will not be described in detail. The conductive agent is selected from various types of conductive carbon, carbon nanotubes and other conductive agent materials known to those skilled in the art, the thickener is selected from sodium carboxymethyl cellulose, the binder is selected from polyvinylidene fluoride, the solvent is selected from deionized water, and the negative electrode current collector is selected from copper foil.
[0045] The present invention has no special restrictions on the proportion of raw materials in the negative electrode slurry, and the proportions and amounts known to those skilled in the art can be used. In the present invention, the negative electrode active material, conductive agent, thickener, and binder are mixed in a mass ratio of 95-97:1-2:0.6-1:1-2.5, and the preferred ratio is 95.4:1.9:0.9:1.8.
[0046] The present invention also provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode comprises the negative electrode active material.
[0047] The negative electrode sheet includes a negative electrode current collector and a negative electrode membrane sheet disposed on at least one surface of the negative electrode current collector and including a negative electrode active material.
[0048] The present invention has no particular limitation on the method for preparing the negative electrode sheet, and any method known to those skilled in the art may be used.
[0049] In the present invention, the negative electrode is preferably prepared according to the following method:
[0050] Mixing the negative electrode active material, the conductive agent, the thickener, the binder and the solvent to obtain a negative electrode slurry;
[0051] The negative electrode slurry is coated on a negative electrode current collector, dried, cold pressed and cut to obtain a negative electrode.
[0052] Wherein, the conductive agent is selected from various types of conductive carbon, carbon nanotubes and other materials, the thickener is selected from sodium carboxymethyl cellulose, the binder is selected from polyvinylidene fluoride, the solvent is selected from deionized water, and the negative electrode current collector is selected from copper foil;
[0053] In the present invention, the positive electrode sheet includes a positive electrode current collector and a positive electrode membrane disposed on at least one surface of the positive electrode current collector and including a positive electrode active material.
[0054] The present invention has no special restrictions on the method for preparing the positive electrode sheet, and any method known to those skilled in the art may be used.
[0055] The present invention has no particular limitation on the specific types of the separator and the electrolyte, and any types known to those skilled in the art may be used.
[0056] The invention obtains a secondary battery with fast charging capability and long cycle life by matching the relationship between the particle size distribution, compaction density and surface area of the battery graphite negative electrode active material.
[0057] In order to further understand the present invention, the negative electrode active material of the secondary battery and the secondary battery provided by the present invention are described below in conjunction with embodiments, and the protection scope of the present invention is not limited by the following embodiments.
[0058] Examples and Comparative Examples
[0059] To prepare the positive electrode sheet, the positive electrode active material lithium iron phosphate, the conductive agent acetylene black, and the binder PVDF are mixed in a mass ratio of 97:2:1, the solvent NMP is added, and the system is stirred under the action of a vacuum mixer until the system is uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain the positive electrode sheet.
[0060] To prepare the negative electrode sheet, the negative electrode active material, the conductive agent acetylene black, the thickener CMC, and the binder SBR are mixed in a mass ratio of 95.4:1.9:0.9:1.8, and then deionized water is added as a solvent. The mixture is stirred in a vacuum mixer until the system is uniform to obtain a negative electrode slurry. The negative electrode slurry is evenly coated on the negative electrode current collector copper foil, dried at room temperature, and then transferred to an oven for further drying. The negative electrode sheet is then obtained by cold pressing and slitting. The specific types and parameters of the negative electrode active materials are shown in Table 1. Figures 1-2 , Figure 1 This is a SEM image of the negative electrode active material used in Example 8; Figure 2 This is a SEM image of the negative electrode active material used in Example 9.
[0061] To prepare an electrolyte, ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.
[0062] A separating film is prepared and a polyethylene film is selected as the separating film.
[0063] To prepare a lithium-ion battery, the positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare cell; the bare cell is placed in an outer packaging shell, and after drying, an electrolyte is injected, and a lithium-ion battery is obtained through vacuum packaging, standing, forming, shaping and other processes.
[0064] Dynamic performance test: At 25°C, the lithium-ion battery prepared in the embodiment and the comparative example was fully charged at xC (1≤x≤6) and fully discharged at 1C for 50 times, and then the lithium-ion battery was fully charged at xC (1≤x≤6), and then the negative electrode was disassembled and the lithium deposition on the surface of the negative electrode was observed. Among them, x was tested from large to small, and the charging rate when the area of lithium deposition on the negative electrode surface was less than 5% was the fast charging capability.
[0065] The test results are shown in Table 1
[0066] Cyclic performance test: At 25°C, the lithium-ion batteries prepared in the examples and comparative examples were fully charged at 1C, discharged to the cut-off voltage, and the discharge capacity was recorded as C1. After standing for 30 minutes, they were charged and discharged at 1C again, and the discharge capacity was recorded as C2. This operation cycle was repeated until C n / C1 is less than 0.8, and n is recorded. The larger n is, the better the cycle performance is. n greater than 2500 cycles indicates excellent cycle performance, n in the range of 2000-2500 cycles indicates average cycle performance, and n less than 2000 cycles indicates poor cycle performance.
[0067] Table 1
[0068]
[0069] As shown in Table 1, in Examples 1-7, 1.0<Z<1.5 has relatively excellent fast charging capability and cycle life. In Examples 8-10, 0.75<Z<1.0 has even better fast charging capability and cycle life. In Comparative Example 1, Z<0.75 has good fast charging capability but poor cycle life. In Comparative Examples 2-4, Z>1.5 has poor fast charging capability and average cycle life.
[0070] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A negative electrode plate of a secondary battery, characterized in that: The negative electrode sheet includes a negative electrode membrane and a negative electrode current collector, the negative electrode membrane includes a negative electrode active material, and the negative electrode membrane satisfies 0.77≤Z≤0.87, wherein Z=0.0452*PD 负 *S 负 *D 50负 , PD 负 is the compaction density of the negative electrode membrane, 1.2 g / cm 3 ≤PD 负 ≤1.8 g / cm 3 ; D 50负 The median particle size of the negative electrode active material is 6.35 μm ≤ D 50负 ≤7.01μm; S 负 is the specific surface area of the negative electrode active material, 1.770m 2 / g≤S 负 ≤2.196 m 2 / g.
2. The negative electrode sheet according to claim 1, characterized in that: The negative electrode active material is selected from one or more of graphite, soft carbon, hard carbon, carbon fiber, and mesophase carbon microspheres.
3. The negative electrode sheet according to claim 2, characterized in that: The graphite is selected from one or more of artificial graphite, natural graphite and modified graphite.
4. The negative electrode sheet according to claim 3, characterized in that: At least a portion of the negative electrode active material is in the form of secondary particles.
5. A method for preparing a negative electrode sheet of a secondary battery according to any one of claims 1 to 4, characterized in that: The process comprises the following steps: mixing the negative electrode active material, the conductive agent, the thickener and the binder, adding the solvent deionized water, stirring until the system is uniform, and obtaining the negative electrode slurry; coating the negative electrode slurry evenly on the negative electrode current collector, drying, and then cold pressing and cutting to obtain the negative electrode sheet.
6. The preparation method according to claim 5, characterized in that: The mass ratio of the negative electrode active material, the conductive agent, the thickener and the binder is 95-97:1-2:0.6-1:1-2.
5.
7. A method for screening negative electrode sheets of secondary batteries, characterized in that: The following steps are involved: First select the median particle size D 50 In the range of 6.35~7.01μm, the specific surface area S 负 1.770~2.196 m 2 / g range of negative electrode active materials, and then control the compaction density of the negative electrode film to be between 1.2 and 1.8 g / cm 3 , so that the negative electrode satisfies 0.77≤Z≤0.87, where Z=0.0452*PD 负 *S 负 *D 50负 .
8. A secondary battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet is the negative electrode sheet according to any one of claims 1 to 4.
